Preliminary study of spider diversity in UiTM Negeri Sembilan Kuala Pilah Campus forest reserve / Farida Hamimi Ahmad Dasran and Nursyazni Abdul Rahim - Ahmad Dasran, Farida Hamimi; Abdul Rahim, Nursyazni
UiTM Negeri Sembilan Kuala Pilah Campus Forest Reserve was a lowland rainforest canopy located in Kampung Beting, Kuala Pilah, which hold various habitats for a wide range of organisms. Many of the species, however, were poorly known and documented. Therefore, a preliminary study was conducted to record the diversity of spider fauna in UiTM Kuala Pilah Campus Forest Reserve in two separate areas using three different methods: hand picking, net sweeping and pitfall traps. The present study resulted in 85 samples of spiders from seven families (Araneidae, Ctenidae, Eutichuridae. Oxyopidae, Pholcidae, Salticidae, and Sparassidae) and 13 genera. There were 29 individuals from four families collected from Site A, and 56 individuals from seven families collected from Site B. Salticidae spiders had dominated both sites with 62% of total samples collected. The second dominant family was Araneidae, which constituted 15% of the samples, followed by Ctenidae (6%), Oxyopidae (6%), Eutichuridae (5%), Sparassidae (4%), and Pholcidae (2%). This ecosystem's spider fauna was qualitatively rich due to diverse microhabitats that represented the high flora and fauna diversity in UiTM Negeri Sembilan Kuala Pilah Campus Forest Reserve. However, the study did not reflect the full spider inventory as fewer sampling periods and areas were conducted. Therefore, additional sampling activities and study periods are anticipated to submit to the inventory of the organisms.